A MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane and its preparation method and application
By using MXene/nitrogen-doped carbon material/bracada fiber sandwich-shaped network structure flexible membrane as electrode material, the problem of separation of active materials during charging and discharging of traditional electrode materials is solved, and efficient, flexible and stable energy storage equipment is achieved.
Patent Information
- Application Number
- CN202310254108.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-03-16
AI Technical Summary
Due to the rigid properties of the electrode materials of traditional energy storage equipment, the active materials are easily separated during the charge and discharge process, limiting the rate capability and cycle stability of the equipment.
The flexible film of MXene/nitrogen doped carbon material/bracada fiber sandwich-shaped network structure is used as the electrode material. The three-dimensional nitrogen doped carbon material is sandwiched through a two-dimensional MXene sheet layer and is interwoven and connected by bracada fibers to form a highly conductive mesh structure.
Improves the flexibility and electrochemical performance of the electrode, increases the specific capacitance, ensures rapid transmission and cycling stability of electrons, and is suitable for portable and wearable electronic devices.
Smart Images

Figure CN116313550B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible film and a preparation method and application thereof, belonging to the field of organic composite electrode materials. Background Art
[0002] Energy, as the foundation and guarantee of scientific and technological development, comes from a wide range of sources, such as traditional non-renewable resources such as coal, oil, and natural gas. It is precisely because of the continuous use of non-renewable energy that an energy crisis has followed, and the search for renewable energy to replace them has become endless. As waste agricultural waste, corn husks are traditionally treated by incineration and landfill, which causes serious damage to the agricultural ecological environment. However, using them as electrode materials for energy storage devices can effectively reduce the impact of agricultural waste on the environment. The characteristics of traditional energy storage devices are mainly large size, low flexibility, and low portability. In addition, during the charge and discharge process, due to the crushing and aggregation of the active material particles of the electrode, there are kinetic problems caused by separation, resulting in limited rate capacity and cycle stability in practical applications. In order to overcome these problems, it has been studied and found that aqueous batteries and supercapacitors have high power density, fast charge and discharge rates, and long cycle life. However, due to the rigid nature of active materials, binders, and conductive materials, most electrodes are rigid. Therefore, when the electrode is repeatedly bent, the active material is easy to separate. Therefore, it is very necessary to use electrodes with good flexibility and high electrochemical performance to meet the needs of portable and wearable electronic devices.
[0003] Therefore, using corn husks as one of the raw materials for flexible electrode materials meets the call for energy conservation and emission reduction, and can also effectively control costs. In addition, the high specific surface area of flexible electrode materials and the flexible aqueous batteries, supercapacitors, etc. prepared therefrom can increase active sites; low internal resistance can improve electron transport; good electrochemical stability can obtain better cycle stability. At present, new electrode materials for flexible aqueous batteries and supercapacitors can not only reduce volume, increase specific surface area, and increase ion accessibility, but also increase the transmission speed of electrons, increase specific capacitance, and reduce safety hazards. With the development of portable electronic devices, the development of flexible aqueous batteries and supercapacitors will become more and more perfect in the future. Summary of the invention
[0004] Purpose of the invention: The first purpose of the present invention is to provide a MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane, the second purpose of the present invention is to provide a method for preparing the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane, the third purpose of the present invention is to provide a flexible membrane electrode comprising the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure, the fourth purpose of the present invention is to provide a solid-state flexible asymmetric aluminum metal sub-battery comprising the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode, the fifth purpose of the present invention is to provide a method for preparing the solid-state flexible asymmetric aluminum metal sub-battery, and the sixth purpose of the present invention is to provide a solid-state flexible supercapacitor comprising a MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane.
[0005] Technical solution: The MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane described in the present invention is a composite flexible membrane material with a sandwich network structure in which two-dimensional MXene layers sandwich three-dimensional nitrogen-doped carbon materials and are interconnected by bract fibers.
[0006] The method for preparing the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane of the present invention comprises the following steps:
[0007] (1) dissolving LiF in a hydrochloric acid solution, adding MAX phase powder, heating and stirring for etching, centrifuging, ultrasonicating, and continuing centrifugation to obtain a monolayer or multilayer dispersed MXene colloidal solution;
[0008] (2) removing the roots of corn husks, cutting them into pieces, ultrasonically washing them, drying them, crushing them, in-situ polymerizing them with aniline, washing them, drying them, and carbonizing them to obtain nitrogen-doped carbon materials;
[0009] (3) washing and drying corn husks, adding them into a NaOH aqueous solution, boiling them for chemical corrosion, washing them with water, and crushing them to obtain a network of highly conductive husk fibers (CHF);
[0010] (4) Adding the nitrogen-doped carbon material to an aqueous solution of sodium dodecylbenzene sulfonate, ultrasonically dispersing the material to enhance the surface activity of the nitrogen-doped carbon material, adding a MXene colloidal solution, ultrasonically treating the material in an ice-water bath, and uniformly dispersing the nitrogen-doped carbon material and MXene in the aqueous solution, then adding the bract fiber dispersion, ultrasonically dispersing the material in an ice-water bath, and uniformly dispersing the nitrogen-doped carbon material, bract fiber, and MXene in the aqueous solution, filtering, washing, and vacuum drying to obtain a sandwich-like network structure MXene / nitrogen-doped carbon material / bract fiber composite flexible membrane, wherein the membrane is composed of two-dimensional MXene sheets sandwiching three-dimensional carbon materials, and the two-dimensional MXene sheets are interwoven and connected together by bract fibers to form an interconnected whole.
[0011] Furthermore, in step (1), the molar concentration of the hydrochloric acid solution is 6-12 mol / L.
[0012] Furthermore, in step (1), the MAX phase powder is a MAX phase powder having a molecular formula of M n+1 AX n A layered compound, wherein M is a transition metal Ti, V, Cr, Zr, Nb, Mo, Hf or Ta, A is a main group element Al, Si, P, S, Ga, Ge, As, Cd, In, Sn, Tl or Pb, X is a C element or a N element, n is the number of layers, and n≥1.
[0013] Furthermore, in step (1), the solid-to-liquid ratio of the LiF, MAX phase powder and hydrochloric acid solution is 1:0.5-10:5-50 g / g / mL.
[0014] Furthermore, in step (1), the temperature for etching with heating and stirring is 20-45° C., and the time for etching with heating and stirring is 12-48 hours.
[0015] Furthermore, in step (1), the centrifugation is repeatedly performed with water until the pH of the supernatant is ≥6.
[0016] Furthermore, in step (1), the ultrasonic treatment is performed for 10-60 min under the protection of argon gas.
[0017] Furthermore, in step (2), the ultrasonic washing is performed by washing with deionized water and anhydrous ethanol for several times.
[0018] Furthermore, in step (2), the in-situ polymerization is carried out by adding a sulfuric acid solution containing aniline and an ammonium persulfate aqueous solution to the corn husk powder aqueous solution and performing a polymerization reaction in an ice-water bath.
[0019] Furthermore, the concentration of sulfuric acid in the sulfuric acid solution containing aniline is 0.5-5 mol / L, and the concentration of aniline is 0.01-10 mol / L.
[0020] Furthermore, the molar ratio of ammonium persulfate to aniline is 10:1-1:10.
[0021] Furthermore, the polymerization reaction time is 1-6 hours.
[0022] Furthermore, in step (2), the washing is performed using tetrahydrofuran, deionized water and ethanol respectively until the pH of the supernatant is ≥ 6.
[0023] Furthermore, in step (2), the drying temperature is 20-80° C., and the drying time is 6-24 hours.
[0024] Furthermore, in step (2), the carbonization is carried out under nitrogen protection at 400-900°C for 1-2h, after which KOH is added in a mass ratio of 1:0.5-10 and the mixture is fully ground, and then calcined at 600-900°C for 0.5-5h.
[0025] Furthermore, in step (3), the concentration of the NaOH aqueous solution is 0.5-5 mol / L.
[0026] Furthermore, in step (3), the solid-to-liquid ratio of the corn husk to the NaOH aqueous solution is 10-100 g / mL.
[0027] Furthermore, in step (3), the boiling time for chemical corrosion is 1-10 hours.
[0028] Furthermore, in step (3), the water washing is performed until the pH value is ≥6.
[0029] Furthermore, in step (3), the particle size of the crushed bract fibers is ≤74 μm.
[0030] Furthermore, in step (4), the mass ratio of the nitrogen-doped carbon material, the bract fiber, and the sodium dodecylbenzene sulfonate is 1:0.1-10:1-100.
[0031] Furthermore, in step (4), the ultrasonic dispersion time is 10-50 min.
[0032] Furthermore, in step (4), the time of the ice-water bath ultrasonic treatment is 15-150 hours.
[0033] Furthermore, in step (4), the vacuum drying temperature is 20-60°C.
[0034] The present invention also includes a MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode, including the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane described in the present invention.
[0035] The present invention also includes a solid-state flexible asymmetric metal ion battery, comprising the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode described in the present invention.
[0036] The method for preparing the solid-state flexible asymmetric aluminum metal sub-battery of the present invention comprises the following steps:
[0037] (1) preparing a metal salt solution;
[0038] (2) Preparation of PVA / metal salt gel;
[0039] (3) PVA / metal salt gel is used as the electrolyte and assembled with the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode described in the present invention to obtain a solid-state flexible asymmetric metal ion battery.
[0040] Furthermore, in step (1), the solid-state flexible asymmetric aluminum metal sub-battery includes a solid-state flexible asymmetric aluminum ion battery, a solid-state flexible asymmetric aluminum-zinc ion battery or a solid-state flexible asymmetric magnesium ion battery, and the metal salt solution is obtained by dissolving a metal salt in water.
[0041] Furthermore, the mass ratio of the metal salt to water is 5-500:5-500.
[0042] Furthermore, in step (2), the PVA / metal salt gel is obtained by mixing metal salt and polyvinyl alcohol (PVA), stirring and heating, and vacuum drying.
[0043] Furthermore, the mass ratio of the metal salt H2SO4 and PVA is 10:1:1-10:1:5.
[0044] Furthermore, the heating and stirring is carried out at 60-90° C. for 1-4 hours.
[0045] Furthermore, the vacuum drying time is 0.5-4h
[0046] Furthermore, in step (3), when assembling the solid-state flexible asymmetric aluminum metal sub-battery, the MXene / carbon material / brassica fiber composite flexible membrane electrode and the end of the aluminum foil not coated with PVA / metal salt gel are connected to the foil surface with conductive silver paste.
[0047] The present invention also includes a solid-state flexible supercapacitor of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane described in the present invention or the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode described in the present invention.
[0048] Furthermore, the preparation process of the solid-state flexible supercapacitor of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible film includes the preparation step of PVA / H2SO4 gel.
[0049] Furthermore, the preparation of the PVA / H2SO4 gel includes mixing H2O, polyvinyl alcohol (PVA), and sulfuric acid (H2SO4), heating and stirring to obtain a colorless and transparent PVA / H2SO4 gel.
[0050] Furthermore, the solid-state flexible supercapacitor includes a solid-state flexible symmetric supercapacitor and a solid-state flexible asymmetric supercapacitor.
[0051] The present invention prepares a MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane, firstly uses MXene and nitrogen-doped carbon material to ultrasonically blend in an ice-water bath, and then adds bract fiber to obtain a MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane material. And the flexible membrane material is used to prepare a flexible membrane electrode and a solid-state flexible asymmetric metal ion battery. The flexible membrane electrode has excellent flexibility and large specific capacitance. MXene is used as a spacer to inhibit the self-stacking of nitrogen-doped carbon materials, and then bract fiber is used to construct a highly conductive mesh structure, and the nitrogen-doped carbon material is tightly anchored on the MXene film, thereby increasing the contact area between MXene and nitrogen-doped carbon materials to ensure the rapid transfer of ions in the solution. Therefore, the prepared sandwich network structure of MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode has good flexibility and electrochemical properties, and is applied to aqueous batteries such as metal ion batteries and (asymmetric) supercapacitors, and has good flexibility and high specific capacitance.
[0052] The present invention uses MXene as a spacer layer of nitrogen-doped carbon materials, solves the self-stacking problem of nitrogen-doped carbon materials to a certain extent, introduces bract fibers to construct a highly conductive mesh structure, and uses bract fibers to construct carbon tubes with abundant oxygen-containing functional groups such as hydroxyl, carboxyl, and oxygen bonds on the surface of MXene and nitrogen-doped carbon materials. These groups have large surface activity, and the hydroxyl, oxygen bond, and fluorine groups on the surface of the nitrogen-doped carbon material and the MXene film activated by the surfactant are tightly anchored together through hydrogen bonding, thereby increasing the contact area between MXene and the nitrogen-doped carbon material, and enhancing the overall stability and electrochemical performance of the flexible membrane electrode of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure, and forming holes through the insertion and extraction of hydrogen ions in the molecular chain, thereby improving the conductivity of the electrode material and providing more active sites, ensuring the rapid transmission of electrons, and helping to improve the power density of the electrode material. And the bract fiber itself also has good flexibility, and the addition of bract fiber can effectively improve the flexibility of the flexible membrane electrode of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure. It can then be used in aqueous batteries such as flexible aluminum ion batteries and flexible supercapacitors, with excellent flexibility and high specific capacitance.
[0053] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0054] (1) The nitrogen doping and husk fiber raw materials of the MXene / nitrogen-doped carbon material / husk fiber sandwich network structure flexible membrane electrode prepared by the present invention are both derived from waste corn husks, which has the advantages of recycling and turning waste into treasure, and can maximize economic benefits and effectively reduce costs. (2) The MXene / nitrogen-doped carbon material / husk fiber sandwich network structure flexible membrane electrode prepared by the present invention has good flexibility and large specific capacitance. The flexible electrode prepared by using the MXene / nitrogen-doped carbon material / husk fiber sandwich network structure flexible membrane of the present invention has a specific capacitance of up to 279F / g when the scanning rate is 100mV / s.
[0055] (3) The MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode prepared by the present invention has excellent flexibility and large specific capacitance. By increasing the interlayer spacing of MXene, the self-stacking problem of MXene materials is solved to a certain extent. By adding a bridging agent, the cycle stability and flexibility of the MXene material are increased. It is then applied to metal ion batteries and has excellent flexibility and high specific capacitance. The specific capacitance of the MXene / nitrogen-doped carbon material / brass fiber / / Al solid-state flexible asymmetric aluminum ion battery assembled using the composite flexible membrane electrode of the present invention is 289F / g at 1A / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1This is a scanning electron microscope image of corn husk fiber (CHF) after chemical corrosion of corn husk in Example 1;
[0057] Figure 2 is a scanning electron microscope image of the crushed bract fiber (CHF) material of Example 1;
[0058] Figure 3 This is a scanning electron microscope image of the carbonized nitrogen-doped corn husk of Example 1;
[0059] Figure 4 This is a scanning electron micrograph of a cross-section of a flexible membrane having a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber of Example 1;
[0060] Figure 5 This is an optical photograph of the flexible film with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber of Example 1;
[0061] Figure 6 This is a schematic diagram of the assembly of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane / / Al flexible asymmetric aluminum ion battery of Example 2;
[0062] Figure 7 CV graphs of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode of Example 2 at different scan rates;
[0063] Figure 8 This is the GCD diagram of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode of Example 2 at different current densities;
[0064] Fig. 9 This is the impedance EIS graph of the flexible membrane electrode of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure of Example 2;
[0065] Fig.10 CV graphs of the flexible membrane electrode of the sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber of Examples 2, 3, and 7 at a scanning speed of 100 mV / s;
[0066] Fig.11 These are the GCD diagrams of the flexible membrane electrodes of MXene / nitrogen-doped carbon material / bract fiber sandwich network structure of Examples 2, 3, and 7 at a current density of 1 A / g. DETAILED DESCRIPTION
[0067] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0068] Example 1 Preparation of MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane
[0069] 1. Preparation of MXene colloidal solution:
[0070] Dissolve 2gLiF in 40mL9mol / L hydrochloric acid solution, slowly add 2gMAX phase (Ti3AlC2) powder and stir for 10min to obtain a suspension. Move the suspension to a 40℃ water bath, stir and keep for 24h. After the reaction is completed, pour the suspension into a centrifuge tube and centrifuge at 3500rpm for 5min. After the centrifugation, pour out the supernatant, add deionized water and shake well, centrifuge repeatedly until the pH of the supernatant is ≥6. Add 120mL of deionized water to the "mud" sample after centrifugation and ultrasonicate for 30min under the protection of argon. Centrifuge the obtained suspension at 3500rpm for 1h. The dark green supernatant after centrifugation is a single-layer or few-layer MXene colloidal solution.
[0071] 2. Preparation of nitrogen-doped carbon materials:
[0072] First, the roots of corn husks were removed and cut into small pieces. After washing with deionized water and washing with anhydrous ethanol for several times, the pieces were dried completely at 80°C in a blast dryer and then crushed into powder in a high-speed multifunctional pulverizer. Secondly, 0.18g corn husk powder was weighed and dissolved in 100mL water, and ultrasonicated for 30min to form a corn husk dispersion. 30mL of sulfuric acid aqueous solution containing aniline monomer (1mol / L H2SO4 solution contains 0.1mol / L aniline monomer) was added, and 20mL of 0.3mol / L ammonium persulfate aqueous solution was added dropwise with a constant pressure dropping funnel under an ice water bath while stirring. The reaction was continued for 2h. After the reaction was completed, the filter cake was filtered and washed with deionized water to remove the remaining aniline monomer on the surface. The filter cake was vacuum dried at room temperature for 12h to obtain in-situ polymerized polyaniline-corn husk powder.
[0073] The above-mentioned polyaniline-corn powder sample was placed in a crucible and placed in a high-temperature tube furnace. Nitrogen was used as the protective gas, the heating rate was 5°C / min, and it was pre-carbonized at 500°C for 1h. After the pre-carbonized sample was fully ground, KOH with a mass ratio of 1:1 was added and fully ground. Then the sample was placed in a tube furnace and calcined at 800°C for 2h to obtain a black product. Finally, the black product was magnetically stirred with a 1M hydrochloric acid solution for 24h, and then washed with tetrahydrofuran, deionized water and ethanol respectively until the pH of the supernatant was about 7. The washed sample was dried in a vacuum drying oven at 60°C for 12h to obtain a nitrogen-doped carbon material.
[0074] 3. Preparation of bract fiber:
[0075] The corn husks were washed and dried, boiled in a 1 mol / L NaOH aqueous solution for 1 h, the corn husk pulp was removed to obtain husk fiber, washed with water until the pH was about 7, dried and crushed (particle size ≤ 74 μm) to obtain husk fiber (CHF).
[0076] 4. Preparation of MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane
[0077] First, add 0.15g of sodium dodecylbenzene sulfonate to 15mL of deionized water as a surfactant, add 15mg of nitrogen-doped carbon material to the above solution, and ultrasonically treat for 10min. Secondly, add 15mL of MXene colloidal solution and mix, ultrasonically treat the mixed solution in an ice-water bath for 15min, then take 15mg of bract fiber and add it to the above solution, ultrasonically treat it in an ice-water bath for 15min, and finally take 10mL of the mixed solution and filter it through a filter membrane with a pore size of 200nm. Vacuum dry at room temperature for 12h to obtain a flexible membrane with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber.
[0078] The bract fibers corroded by the NaOH aqueous solution prepared in this example were analyzed by scanning electron microscope. Figure 1 As shown by Figure 1 It can be seen that after chemical corrosion, the fiber structure of corn husk is arranged regularly; the scanning electron microscope analysis of the husk fiber obtained after crushing shows the following results: Figure 2 As shown by Figure 2 It can be seen that the fiber structure of the crushed husks is interwoven with each other to present a spatial network, which provides a convenient channel for subsequent bridging of horizontal MXene flakes, increasing the contact area between MXene and corn husks, and rapid transfer of electrons. It is beneficial to improve the overall stability and flexibility of the composite membrane electrode material without sacrificing electrical performance.
[0079] The nitrogen-doped carbon material prepared in this example was analyzed by scanning electron microscopy. Figure 3 shown. Figure 3 This is a scanning electron microscope image of nitrogen-doped corn husks after carbonization. Figure 3 It can be seen that the nitrogen-doped carbon material has a larger ion channel, and polyaniline grows evenly on the surface of the nitrogen-doped corn husk carbon tube wall, which increases the active sites and provides channels for the transport of ions, which is beneficial to the improvement of the capacitance performance of the material.
[0080] The cross section of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible film prepared in this example was analyzed by scanning electron microscopy. Figure 4 shown. Figure 4 This is a scanning electron micrograph of a cross-section of a flexible membrane having a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber of Example 1. Figure 4 It can be seen that the nitrogen-doped carbon material has an irregular shape, and the contact between the three-dimensional nitrogen-doped carbon material and the two-dimensional MXene sheets is in a point-to-point form. The interwoven bract fibers form a three-dimensional network structure on the surface of MXene and nitrogen-doped carbon materials. This special structure not only anchors the nitrogen-doped carbon material to the MXene sheets, increasing their contact area, but also bridges adjacent MXene sheets, allowing the material to form a sandwich network structure, so that electrons can be easily transmitted through the coherent conductive network.
[0081] The optical photograph of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible film prepared in this example is shown in FIG. Figure 5 As shown, a) is the unfolded view; b), c), d) are all bent views; e) is the curled view; f) is the re-unfolded view. Figure 5 It can be seen that after being bent and curled at different angles and then unfolded, the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane has no obvious creases or deformation compared with before bending and folding. Therefore, the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane has excellent flexibility.
[0082] Example 2 Preparation of MXene / nitrogen-doped carbon material / brassica fiber solid-state flexible asymmetric aluminum ion battery
[0083] 1. Preparation of AlCl3 solution
[0084] Dissolve 24.15 g of AlCl3·6H2O in 10 g of H2O to obtain AlCl3 solution.
[0085] 2. Preparation of PVA / AlCl3 gel
[0086] Mix 60g of H2O and 6g of polyvinyl alcohol (PVA) and heat to 85°C, stir for 20min to obtain a colorless and transparent PVA solution. Take 5mL of PVA solution, add 10mL of AlCl3 solution, stir for 2h to obtain the preparation of PVA / AlCl3 gel.
[0087] 3. MXene / nitrogen-doped carbon material / bracte fiber solid-state flexible asymmetric aluminum ion battery assembly test:
[0088] The MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane in Example 1 was cut into 2×1 cm pieces as an electrode, and the cut MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode was placed in the cooled PVA / AlCl3 gel for 5 minutes. Then a 2×1 cm aluminum sheet was stacked on the other side covered with the PVA / AlCl3 gel electrolyte and placed in an oven at 30°C for 1 hour, and then dried at room temperature for 30 minutes. The two sides of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode and the aluminum sheet electrode without PVA / AlCl3 gel electrolyte were connected to the pole ears with conductive silver paste, and an aluminum-plastic film was coated on the outer layer to obtain a MXene / nitrogen-doped carbon material / bract fiber / / Al solid-state flexible asymmetric aluminum ion battery, and the prepared MXene / nitrogen-doped carbon material / bract fiber / / Al solid-state flexible asymmetric aluminum ion battery was subjected to linear cyclic voltammetry test and constant current charge and discharge test. The assembly process is as follows Figure 6 shown.
[0089] The MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode prepared in this example was subjected to cyclic voltammetry tests at scan rates of 10 mV / s, 20 mV / s, 40 mV / s, 60 mV / s, 80 mV / s, and 100 mV / s. The results are as follows: Figure 7 shown.
[0090] Figure 7 CV curve of the MXene / nitrogen-doped carbon material / bracte fiber sandwich network structure flexible membrane electrode in Example 2, Figure 7 It can be seen that the oxidation peak and reduction peak of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode also move to high voltage and low voltage with the increase of scanning rate, but the amplitude of the movement is not large, indicating that the polarization phenomenon of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode is not obvious at high scanning rate, and at the same time, it shows that the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode has good rate performance. Through calculation, it can be seen that at a scanning rate of 100mV / s, the specific capacitance can reach 265F / g. And the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode shows good flexibility. The assembled MXene / nitrogen-doped carbon material / bract fiber / / Al flexible asymmetric aluminum ion battery has a specific capacitance of 56F / g at 0.5A / g and shows good flexibility.
[0091] The MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode prepared in this example was subjected to constant current charge and discharge tests at current densities of 1A / g, 2A / g, 3A / g, 4A / g, and 5A / g. The results are as follows: Figure 8 As shown. Figure 8 It can be seen that as the current density decreases, the charging and discharging time of the flexible membrane electrode with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber increases accordingly. The charging curve and the discharge curve present a relatively similar isosceles triangle, and there is no obvious voltage rise or voltage drop.
[0092] The AC impedance test of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode obtained in this embodiment is shown in Figure 9. Fig. 9 It can be seen that the angle between the straight line of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode in the low-frequency region and the X-axis is close to 90°, indicating that the electron transfer rate is very fast during the reaction process, indicating that the two-dimensional material MXene acts as a spacer layer, which effectively alleviates the self-accumulation of nitrogen-doped carbon materials and increases the interlayer spacing; the bract fiber also effectively bridges the MXene plane and the nitrogen-doped carbon material, increasing the contact area between the two and ensuring the rapid transfer of electrons.
[0093] Example 3 The experimental process for preparing a flexible membrane of a MXene / nitrogen-doped carbon material / bract fiber sandwich network structure is the same as that of Example 1, except that the addition of nitrogen-doped carbon material is changed, specifically: 5 mg.
[0094] First, add 0.15g of sodium dodecylbenzene sulfonate to 15mL of deionized water as a surfactant, add 5mg of nitrogen-doped carbon material to the above solution, and ultrasonically treat for 10min. Secondly, add 15mL of MXene colloidal solution and mix, ultrasonically treat the mixed solution in an ice-water bath for 15min, then take 15mg of bract fiber and add it to the above solution, ultrasonically treat it in an ice-water bath for 15min, and finally take 10mL of the mixed solution and filter it through a filter membrane with a pore size of 200nm. Vacuum dry at room temperature for 12h to obtain a flexible membrane with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber.
[0095] The preparation and testing of MXene / nitrogen-doped carbon material / bract fiber / / Al flexible asymmetric aluminum ion battery are the same as in Example 2.
[0096] The MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery prepared in this embodiment was subjected to cyclic voltammetry test, and the results showed that the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode had a specific capacitance of 103F / g at a scan rate of 100mV / s, and showed good flexibility. The assembled MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery had a specific capacitance of 38F / g at 0.5A / g, and showed good flexibility, so the addition of nitrogen-doped carbon material would affect the flexibility of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode.
[0097] Example 4 The experimental process for preparing a flexible membrane with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber is the same as that of Example 1, except that the addition of nitrogen-doped carbon material is changed, specifically: 10 mg.
[0098] First, add 0.15g of sodium dodecylbenzene sulfonate to 15mL of deionized water as a surfactant, add 10mg of nitrogen-doped carbon material to the above solution, and ultrasonically treat for 10min. Secondly, add 15mL of MXene colloidal solution and mix, ultrasonically treat the mixed solution in an ice-water bath for 15min, then take 15mg of bract fiber and add it to the above solution, ultrasonically treat it in an ice-water bath for 15min, and finally take 10mL of the mixed solution and filter it through a filter membrane with a pore size of 200nm. Vacuum dry at room temperature for 12h to obtain a flexible membrane with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber.
[0099] The preparation and testing of MXene / nitrogen-doped carbon material / bract fiber / / Al flexible asymmetric aluminum ion battery are the same as in Example 2.
[0100] The MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery prepared in this embodiment was subjected to cyclic voltammetry test, and the results showed that the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode had a specific capacitance of 126F / g at a scan rate of 100mV / s, and showed good flexibility. The assembled MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery had a specific capacitance of 42F / g at 0.5A / g, and showed good flexibility, so the addition of nitrogen-doped carbon material would affect the flexibility of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode.
[0101] Example 5 The experimental process for preparing a flexible membrane with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber is the same as that of Example 1, except that the addition of nitrogen-doped carbon material is changed, specifically: 20 mg.
[0102] First, add 0.15g of sodium dodecylbenzene sulfonate to 15mL of deionized water as a surfactant, add 20mg of nitrogen-doped carbon material to the above solution, and ultrasonically treat for 10min. Secondly, add 15mL of MXene colloidal solution and mix, ultrasonically treat the mixed solution in an ice-water bath for 15min, then take 15mg of bract fiber and add it to the above solution, ultrasonically treat it in an ice-water bath for 15min, and finally take 10mL of the mixed solution and filter it through a filter membrane with a pore size of 200nm. Vacuum dry at room temperature for 12h to obtain a MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane.
[0103] The preparation and testing of MXene / nitrogen-doped carbon material / bract fiber / / Al flexible asymmetric aluminum ion battery are the same as in Example 2.
[0104] The MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery prepared in this embodiment was subjected to cyclic voltammetry test, and the results showed that the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode had a specific capacitance of 243F / g at a scan rate of 100mV / s, and showed good flexibility. The assembled MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery had a specific capacitance of 53F / g at 0.5A / g, and showed good flexibility, so the addition of nitrogen-doped carbon material would affect the flexibility of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode.
[0105] Example 6 The experimental process for preparing a flexible membrane with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber is the same as that of Example 1, except that the addition of nitrogen-doped carbon material is changed, specifically: 25 mg.
[0106] First, add 0.15g of sodium dodecylbenzene sulfonate to 15mL of deionized water as a surfactant, add 25mg of nitrogen-doped carbon material to the above solution, and ultrasonically treat for 10min. Secondly, add 15mL of MXene colloidal solution and mix, ultrasonically treat the mixed solution in an ice-water bath for 15min, then take 15mg of bract fiber and add it to the above solution, ultrasonically treat it in an ice-water bath for 15min, and finally take 10mL of the mixed solution and filter it through a filter membrane with a pore size of 200nm. Vacuum dry at room temperature for 12h to obtain a flexible membrane with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber.
[0107] The preparation and testing of MXene / nitrogen-doped carbon material / bract fiber / / Al flexible asymmetric aluminum ion battery are the same as in Example 2.
[0108] The MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery prepared in this embodiment was subjected to cyclic voltammetry test, and the results showed that the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane had a specific capacitance of 187F / g at a scan rate of 100mV / s, and showed good flexibility. The assembled MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery had a specific capacitance of 46F / g at 0.5A / g, and showed good flexibility, so the addition of nitrogen-doped carbon material would affect the flexibility of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode.
[0109] Example 7 The experimental process for preparing a flexible membrane with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber is the same as that of Example 1, except that the amount of bract fiber added is changed to 5 mg.
[0110] First, add 0.15g of sodium dodecylbenzene sulfonate to 15mL of deionized water as a surfactant, add 15mg of nitrogen-doped carbon material to the above solution, and ultrasonically treat for 10min. Secondly, add 15mL of MXene colloidal solution and mix, ultrasonically treat the mixed solution in an ice-water bath for 15min, then take 5mg of bract fiber and add it to the above solution, ultrasonically treat it in an ice-water bath for 15min, and finally take 10mL of the mixed solution and filter it through a filter membrane with a pore size of 200nm. Vacuum dry at room temperature for 12h to obtain a MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane.
[0111] The preparation and testing of MXene / nitrogen-doped carbon material / bract fiber / / Al flexible asymmetric aluminum ion battery are the same as in Example 2.
[0112] The MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery prepared in this embodiment was subjected to cyclic voltammetry test, and the results showed that the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode had a specific capacitance of 113F / g at a scan rate of 100mV / s, and showed good flexibility. The assembled MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery had a specific capacitance of 39F / g at 0.5A / g, and showed good flexibility, so the addition of nitrogen-doped carbon material would affect the flexibility of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode.
[0113] The CV curves of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode obtained in this example are compared with those of the composite flexible membrane electrodes of Examples 2 and 3 at a scan rate of 100 mV / s. The results are as follows: Fig.10As shown. Fig.10 It can be seen that compared with Example 3, the voltage window of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode in this embodiment is expanded, and the positions of the oxidation and reduction peaks are more obvious, indicating that with the increase of nitrogen-doped carbon material, the electrochemical performance of the composite flexible membrane electrode is enhanced, and the stability performance is also enhanced, but the oxidation and reduction peaks move to the right, indicating that the reduction of bract fibers reduces the effective contact area between the MXene plane and the carbon material, and reduces the ion accessibility. Compared with Example 3, the voltage window of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode in Example 2 is expanded, and the positions of the oxidation and reduction peaks are more obvious, indicating that with the increase of carbon material, the electrochemical performance of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode is enhanced, and the stability performance is also enhanced; the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode in Example 2 has the strongest electrochemical performance and the best stability performance; compared with this example, the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode in Example 2 has a shifted left position at the same scanning speed, indicating that with the increase of bract fibers, the contact area between the MXene plane of the composite flexible membrane electrode and the nitrogen-doped carbon material increases, the ion accessibility also increases accordingly, and the electrochemical performance is enhanced. Compared with the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode of Example 3 and this example, at the same scanning speed, the position of the redox peak shifts to the left, indicating that with the increase of bract fibers, the contact area between the MXene plane of the composite flexible membrane electrode and the nitrogen-doped carbon material increases, the ion accessibility also increases accordingly, and the electrochemical performance is enhanced.
[0114] The GCD curves of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode obtained in this example are compared with those of the composite flexible membrane electrodes of Examples 2 and 3 at a current density of 1 mA / g. The results are as follows: Fig.11 As shown. Fig.11It can be seen that the voltage window of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode of this embodiment is expanded compared with that of Example 3. With the increase of fiber material, the charge and discharge time of the composite flexible membrane electrode is enhanced, and there is no obvious voltage rise and voltage drop. It shows that the addition of nitrogen-doped carbon material and bract fiber can effectively enhance the electrical properties of the composite flexible membrane electrode material. Compared with Example 3 and this embodiment, the voltage window of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode of Example 2 is expanded. With the increase of fiber material and nitrogen-doped carbon material, the charge and discharge time of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode is enhanced, and there is no obvious voltage rise and voltage drop. It shows that the addition of nitrogen-doped carbon material and bract fiber can effectively enhance the electrical properties of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode material.
[0115] Example 8 The experimental process for preparing a flexible membrane with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber is the same as that of Example 1, except that the addition of bract fiber is changed, specifically: 10 mg.
[0116] First, add 0.15g of sodium dodecylbenzene sulfonate to 15mL of deionized water as a surfactant, add 15mg of nitrogen-doped carbon material to the above solution, and ultrasonically treat for 10min. Secondly, add 15mL of MXene colloidal solution and mix, ultrasonically treat the mixed solution in an ice-water bath for 15min, then take 10mg of bract fiber and add it to the above solution, ultrasonically treat it in an ice-water bath for 15min, and finally take 10mL of the mixed solution and filter it through a filter membrane with a pore size of 200nm. Vacuum dry at room temperature for 12h to obtain a flexible membrane with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber.
[0117] The preparation and testing of MXene / nitrogen-doped carbon material / bract fiber / / Al flexible asymmetric aluminum ion battery are the same as in Example 2.
[0118] The MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery prepared in this embodiment was subjected to cyclic voltammetry test, and the results showed that the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode had a specific capacitance of 172F / g at a scan rate of 100mV / s, and showed good flexibility. The assembled MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery had a specific capacitance of 44F / g at 0.5A / g, and showed good flexibility, so the addition of nitrogen-doped carbon material would affect the flexibility of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode.
[0119] Example 9 The experimental process for preparing a flexible membrane with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber is the same as that of Example 1, except that the addition of bract fiber is changed, specifically: 20 mg.
[0120] First, add 0.15g of sodium dodecylbenzene sulfonate to 15mL of deionized water as a surfactant, add 15mg of nitrogen-doped carbon material to the above solution, and ultrasonically treat it for 10min. Secondly, add 15mL of MXene colloidal solution and mix, ultrasonically treat the mixed solution in an ice-water bath for 15min, then take 20mg of bract fiber and add it to the above solution, ultrasonically treat it in an ice-water bath for 15min, and finally take 10mL of the mixed solution and filter it through a filter membrane with a pore size of 200nm. Vacuum dry at room temperature for 12h to obtain a flexible membrane with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber.
[0121] The preparation and testing of MXene / nitrogen-doped carbon material / bract fiber / / Al flexible asymmetric aluminum ion battery are the same as in Example 2.
[0122] The MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery prepared in this embodiment was subjected to cyclic voltammetry test, and the results showed that the MXene / nitrogen-doped carbon material / brass fiber composite flexible membrane electrode had a specific capacitance of 232F / g at a scan rate of 100mV / s, and showed good flexibility. The assembled MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery had a specific capacitance of 53F / g at 0.5A / g, and showed good flexibility, so the addition of nitrogen-doped carbon material would affect the flexibility of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode.
[0123] Example 10 The experimental process for preparing a flexible membrane with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber is the same as that of Example 1, except that the addition of bract fiber is changed, specifically: 25 mg.
[0124] First, add 0.15g of sodium dodecylbenzene sulfonate to 15mL of deionized water as a surfactant, add 15mg of nitrogen-doped carbon material to the above solution, and ultrasonically treat for 10min. Secondly, add 15mL of MXene colloidal solution and mix, ultrasonically treat the mixed solution in an ice-water bath for 15min, then take 25mg of bract fiber and add it to the above solution, ultrasonically treat it in an ice-water bath for 15min, and finally take 10mL of the mixed solution and filter it through a filter membrane with a pore size of 200nm. Vacuum dry at room temperature for 12h to obtain a flexible membrane with a sandwich network structure of MXene / nitrogen-doped carbon material / bract fiber.
[0125] The preparation and testing of MXene / nitrogen-doped carbon material / bract fiber / / Al flexible asymmetric aluminum ion battery are the same as in Example 2.
[0126] The MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery prepared in this embodiment was subjected to cyclic voltammetry test, and the results showed that the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode had a specific capacitance of 196F / g at a scan rate of 100mV / s, and showed good flexibility. The assembled MXene / nitrogen-doped carbon material / brass fiber / / Al flexible asymmetric aluminum ion battery had a specific capacitance of 49F / g at 0.5A / g, and showed good flexibility, so the addition of nitrogen-doped carbon material will affect the flexibility of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode.
[0127] Example 11 Preparation of MXene / nitrogen-doped carbon material / brassica fiber solid-state flexible asymmetric zinc ion battery
[0128] 1. Preparation of ZnCl2 solution
[0129] Dissolve 1.36 g ZnCl2 in 10 g H2O to obtain a ZnCl2 solution.
[0130] 2. Preparation of PVA / ZnCl2 gel
[0131] Mix 60gH2O and 6g polyvinyl alcohol (PVA) and heat to 85℃, stir for 20min to obtain a colorless and transparent PVA solution. Take 5mL PVA solution, add 10mL ZnCl2 solution, stir for 2h to obtain the preparation of PVA / ZnCl2 gel.
[0132] 3. MXene / nitrogen-doped carbon material / bracte fiber solid-state flexible asymmetric zinc-ion battery assembly test:
[0133] The MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane in Example 1 was cut into 2×1 cm as an electrode, and the cut MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode was placed in the cooled PVA / ZnCl2 gel for 5 minutes. Then a 2×1 cm zinc sheet was stacked on the other side covered with PVA / ZnCl2 gel electrolyte and placed in an oven at 30°C for 1 hour, and then dried at room temperature for 30 minutes. The MXene / carbon material / brass fiber composite flexible membrane electrode and the zinc sheet electrode without PVA / ZnCl2 gel electrolyte were connected to the pole ears with conductive silver paste, and the outer layer was coated with aluminum-plastic film to obtain a MXene / nitrogen-doped carbon material / brass fiber / / Zn solid-state flexible asymmetric zinc ion battery, and the prepared MXene / nitrogen-doped carbon material / brass fiber / / Zn solid-state flexible asymmetric zinc ion battery was subjected to linear cyclic voltammetry test and constant current charge and discharge test.
[0134] The MXene / nitrogen-doped carbon material / brass fiber / / Zn flexible asymmetric zinc ion battery prepared in this embodiment was subjected to cyclic voltammetry test, and the results showed that the MXene / nitrogen-doped carbon material / brass fiber composite flexible electrode had a specific capacitance of 240F / g at a scan rate of 100mV / s, and showed good flexibility. The assembled MXene / nitrogen-doped carbon material / brass fiber / / Zn flexible asymmetric zinc ion battery had a specific capacitance of 51F / g at 0.5A / g, and showed good flexibility, so the addition of nitrogen-doped carbon material would affect the flexibility of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode.
[0135] Example 12 Preparation of MXene / nitrogen-doped carbon material / brassica fiber solid-state flexible asymmetric magnesium ion battery 1. Preparation of MgCl2 solution
[0136] Dissolve 1.36 g MgCl2 in 10 g H2O to obtain MgCl2 solution.
[0137] 2. Preparation of PVA / MgCl2 gel
[0138] Mix 60g H2O and 6g polyvinyl alcohol (PVA) and heat to 85°C, stir for 20min to obtain a colorless and transparent PVA solution. Take 5mL PVA solution, add 10mL MgCl2 solution, stir for 2h to obtain the preparation of PVA / MgCl2 gel.
[0139] 3. MXene / nitrogen-doped carbon material / bracte fiber solid-state flexible asymmetric zinc-ion battery assembly test:
[0140] The MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane in Example 1 was cut into 2×1 cm as an electrode, and the cut MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode was placed in the cooled PVA / MgCl2 gel for 5 minutes. Then a 2×1 cm magnesium sheet was stacked on the other side covered with PVA / MgCl2 gel electrolyte and placed in an oven at 30°C for 1 hour, and then dried at room temperature for 30 minutes. The two sides of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode and the magnesium sheet electrode without PVA / MgCl2 gel electrolyte were connected to the pole ears with conductive silver paste, and the outer layer was coated with aluminum-plastic film to obtain a MXene / nitrogen-doped carbon material / brass fiber / / Mg solid-state flexible asymmetric magnesium ion battery, and the prepared MXene / nitrogen-doped carbon material / brass fiber / / Mg solid-state flexible asymmetric magnesium ion battery was subjected to linear cyclic voltammetry test and constant current charge and discharge test.
[0141] The MXene / nitrogen-doped carbon material / brass fiber / / Mg solid-state flexible asymmetric magnesium-ion battery prepared in this embodiment was subjected to a cyclic voltammetry test. The results showed that the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode had a specific capacitance of 241F / g at a scan rate of 100mV / s, and showed good flexibility. The assembled MXene / nitrogen-doped carbon material / brass fiber / / Mg solid-state flexible asymmetric magnesium-ion battery had a specific capacitance of 52F / g at 0.5A / g, and showed good flexibility, so the addition of nitrogen-doped carbon material would affect the flexibility of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode.
[0142] Example 13 Preparation of MXene / nitrogen-doped carbon material / bract fiber / / MXene / nitrogen-doped carbon material / bract fiber solid-state flexible symmetric supercapacitor
[0143] 1. Preparation of PVA / H2SO4 gel:
[0144] Mix 60 g H2O, 6 g polyvinyl alcohol (PVA), and 6 g 98% sulfuric acid (H2SO4), heat to 85°C, and stir for 20 min to obtain a colorless and transparent PVA / H2SO4 gel.
[0145] 2. MXene / nitrogen-doped carbon material / bract fiber / / MXene / nitrogen-doped carbon material / bract fiber solid-state flexible symmetrical supercapacitor assembly test:
[0146] The MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane in Example 1 was cut into 2×1 cm as an electrode, and the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode was placed in the cooled PVA / H2SO4 gel for 5 minutes. Then two sheets of MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrodes coated with PVA / H2SO4 gel electrolyte were stacked and placed in an oven at 30°C for 1 hour, and then dried at room temperature for 30 minutes. The two sides of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode without PVA / H2SO4 gel electrolyte were connected to the pole ears with conductive silver paste, and the outer layer was coated with aluminum-plastic film to obtain MXene / nitrogen-doped carbon material / bract fiber / / MXene / nitrogen-doped carbon material / bract fiber solid-state flexible symmetric supercapacitor, and the prepared MXene / nitrogen-doped carbon material / bract fiber / / MXene / nitrogen-doped carbon material / bract fiber solid-state flexible symmetric supercapacitor was subjected to linear cyclic voltammetry test and constant current charge and discharge test.
[0147] The MXene / nitrogen-doped carbon material / brass fiber / / MXene / nitrogen-doped carbon material / brass fiber solid-state flexible symmetric supercapacitor prepared in this embodiment was subjected to cyclic voltammetry test, and the results showed that the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode had a specific capacitance of 239F / g at a scan rate of 100mV / s, and showed good flexibility. The assembled MXene / nitrogen-doped carbon material / brass fiber / / MXene / nitrogen-doped carbon material / brass fiber solid-state flexible symmetric supercapacitor had a specific capacitance of 47F / g at 0.5A / g, and showed good flexibility, so the addition of nitrogen-doped carbon material would affect the flexibility of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode.
[0148] Example 14 Preparation of MXene / nitrogen-doped carbon material / bract fiber / / C (carbon paper) solid-state flexible asymmetric supercapacitor
[0149] 1. Preparation of PVA / H2SO4 gel
[0150] Mix 60 g H2O, 6 g polyvinyl alcohol (PVA), and 6 g 98% sulfuric acid (H2SO4), heat to 85°C, and stir for 20 min to obtain a colorless and transparent PVA / H2SO4 gel.
[0151] 2. MXene / nitrogen-doped carbon material / bract fiber / / C solid-state flexible asymmetric supercapacitor assembly test:
[0152] The MXene / nitrogen-doped carbon material / husk fiber sandwich network structure flexible membrane in Example 1 was cut into 2×1 cm as an electrode, and the MXene / nitrogen-doped carbon material / husk fiber sandwich network structure flexible membrane electrode was placed in the cooled PVA / H2SO4 gel for 5 minutes. Then a 2×1 cm carbon paper electrode was stacked on the other side covered with PVA / H2SO4 gel electrolyte and placed in an oven at 30°C for 1 hour, and then dried at room temperature for 30 minutes. The MXene / nitrogen-doped carbon material / husk fiber sandwich network structure flexible membrane electrode and the carbon paper electrode without PVA / H2SO4 gel electrolyte were connected to the pole ears with conductive silver paste, and the outer layer was coated with aluminum-plastic film to obtain a MXene / nitrogen-doped carbon material / husk fiber / / C solid-state flexible asymmetric magnesium ion battery, and the prepared MXene / nitrogen-doped carbon material / husk fiber / / C solid-state flexible asymmetric magnesium ion battery was subjected to linear cyclic voltammetry test and constant current charge and discharge test.
[0153] The MXene / nitrogen-doped carbon material / brass fiber / / C (carbon paper) solid-state flexible asymmetric supercapacitor prepared in this embodiment was subjected to cyclic voltammetry test, and the results showed that the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode had a specific capacitance of 233F / g at a scan rate of 100mV / s, and showed good flexibility. The assembled MXene / nitrogen-doped carbon material / brass fiber / / C (carbon paper) solid-state flexible asymmetric supercapacitor had a specific capacitance of 43F / g at 0.5A / g, and showed good flexibility, so the addition of nitrogen-doped carbon material would affect the flexibility of the MXene / nitrogen-doped carbon material / brass fiber sandwich network structure flexible membrane electrode.
Claims
1. A MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane, characterized in that: The MXene / nitrogen-doped carbon material / bract fiber composite flexible membrane is a composite flexible membrane material with a sandwich-like network structure in which two-dimensional MXene sheets sandwich three-dimensional nitrogen-doped carbon materials and are interwoven and connected by bract fibers. The preparation method comprises the following steps: (1) Dissolve LiF in hydrochloric acid solution, add MAX phase powder, heat and stir for etching, centrifuge, ultrasonicate, and continue centrifugation to obtain MXene colloidal solution; (2) removing the roots of corn husks, cutting them into pieces, ultrasonically washing them, drying them, crushing them, in-situ polymerizing them with aniline, washing them, drying them, and carbonizing them to obtain nitrogen-doped carbon materials; (3) washing the corn husks, drying them, adding them into a NaOH aqueous solution, boiling them for chemical corrosion, washing them with water, and crushing them to obtain husk fibers; (4) Add the nitrogen-doped carbon material to the sodium dodecylbenzene sulfonate aqueous solution, ultrasonically disperse it, add the MXene colloidal solution, ultrasonically treat it in an ice-water bath, then add the bract fiber dispersion solution, ultrasonically disperse it, filter it, wash it, and vacuum dry it to obtain a MXene / nitrogen-doped carbon material / bract fiber composite flexible membrane.
2. The method for preparing the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane according to claim 1, characterized in that: The following steps are involved: (1) Dissolve LiF in hydrochloric acid solution, add MAX phase powder, heat and stir for etching, centrifuge, ultrasonicate, and continue centrifugation to obtain MXene colloidal solution; (2) removing the roots of corn husks, cutting them into pieces, ultrasonically washing them, drying them, crushing them, in-situ polymerizing them with aniline, washing them, drying them, and carbonizing them to obtain nitrogen-doped carbon materials; (3) washing the corn husks, drying them, adding them into a NaOH aqueous solution, boiling them for chemical corrosion, washing them with water, and crushing them to obtain husk fibers; (4) Add the nitrogen-doped carbon material to the sodium dodecylbenzene sulfonate aqueous solution, ultrasonically disperse it, add the MXene colloidal solution, ultrasonically treat it in an ice-water bath, then add the bract fiber dispersion solution, ultrasonically disperse it, filter it, wash it, and vacuum dry it to obtain a MXene / nitrogen-doped carbon material / bract fiber composite flexible membrane.
3. The preparation method according to claim 2, characterized in that: In step (1), the molar concentration of the hydrochloric acid solution is 6-12 mol / L, and the MAX phase powder has a molecular formula of M n+1 AX n A layered compound, wherein M is a transition metal Ti, V, Cr, Zr, Nb, Mo, Hf or Ta, A is a main group element Al, Si, P, S, Ga, Ge, As, Cd, In, Sn, Tl or Pb, X is a C element or a N element, n is the number of layers, and n≥1; the solid-liquid ratio of the MAX phase powder, LiF and hydrochloric acid solution is 1:0.5-10:5-50g / g / mL, the temperature for heating and stirring for etching is 20-45°C, and the time for heating and stirring for etching is 12-48h; the centrifugation is repeatedly performed with water until the pH of the supernatant is ≥6; the ultrasound is performed under the protection of argon for 10-60min.
4. The preparation method according to claim 2, characterized in that: In step (2), the ultrasonic washing is washing with deionized water and washing with anhydrous ethanol for several times; the in-situ polymerization is adding aniline-containing sulfuric acid solution and ammonium persulfate aqueous solution to the corn husk powder aqueous solution for polymerization reaction in an ice-water bath, the concentration of sulfuric acid in the aniline-containing sulfuric acid solution is 0.5-5 mol / L, and the concentration of aniline is 0.01-10 mol / L; the molar ratio of ammonium persulfate to aniline is 10:1-1:10, and the polymerization reaction time is 1-6 hours; the washing is washing with tetrahydrofuran, deionized water and ethanol respectively until the pH of the supernatant is ≥6, the drying temperature is 20-80°C, and the drying time is 6-24 hours; the carbonization is pre-carbonized at 400-900°C for 1-2 hours under nitrogen protection, and after pre-carbonization, KOH with a mass ratio of 1:0.5-10 is added for sufficient grinding, and then calcined at 600-900°C for 0.5-5 hours.
5. The preparation method according to claim 2, characterized in that: In step (3), the concentration of the NaOH aqueous solution is 0.5-5 mol / L, the solid-liquid ratio of the corn husk to the NaOH aqueous solution is 10-100 g / mL, the boiling time for chemical corrosion is 1-10 h, the water washing is performed until the pH value is ≥ 6, and the particle size of the crushed husk fiber is ≤ 74 μm; in step (4), the mass ratio of the nitrogen-doped carbon material, husk fiber, and sodium dodecylbenzene sulfonate is 1:0.1-10:1-100, the time for each ultrasonic dispersion is 10-50 min, the mass ratio of MXene to nitrogen-doped carbon material is 100:1-1:100, the time for the ice-water bath ultrasonic treatment is 15-150 min, and the vacuum drying temperature is 20-60 ° C.
6. A MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode, characterized in that: It comprises the flexible film of the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure as described in claim 1.
7. A solid-state flexible asymmetric metal ion battery, characterized in that: A flexible membrane electrode comprising the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure as described in claim 6.
8. A method for preparing the solid-state flexible asymmetric metal ion battery according to claim 7, characterized in that: The following steps are involved: (1) preparing a metal salt solution; (2) Preparation of PVA / metal salt gel; (3) PVA / metal salt gel is used as the electrolyte and assembled with the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode as described in claim 6 to obtain a solid-state flexible asymmetric metal ion battery.
9. The method for preparing a solid-state flexible asymmetric metal ion battery according to claim 8, characterized in that: The solid-state flexible asymmetric metal ion battery comprises a solid-state flexible asymmetric aluminum ion battery, a solid-state flexible asymmetric aluminum-zinc ion battery or a solid-state flexible asymmetric magnesium ion battery. In step (1), the metal salt solution is obtained by dissolving a metal salt in water. In step (2), the PVA / metal salt gel is obtained by mixing a metal salt and polyvinyl alcohol (PVA), stirring and heating.
10. A solid-state flexible supercapacitor comprising the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane described in claim 1 or the MXene / nitrogen-doped carbon material / bract fiber sandwich network structure flexible membrane electrode described in claim 6.
Citation Information
Patent Citations
Preparation method of MXene nanocellulose carbon nanotube composite material
CN114605708A